ANALISIS PENERAPAN MODEL RADEC (READ, ANSWER, DISCUSS, EXPLAIN, CREATE) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Silvi Samrotul Fuadah; Yeni Dwi Kurino; Mahpudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical problem-solving ability is an essential competency that should be developed from the elementary school level. One learning model with the potential to foster this ability is the Read, Answer, Discuss, Explain, and Create (RADEC) model. This study aims to analyze the characteristics of previous research and examine the contribution of the RADEC model to elementary school students' mathematical problem-solving ability. The study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Literature was retrieved from the Google Scholar and Scopus databases, and the articles were screened based on predetermined inclusion and exclusion criteria, resulting in 15 eligible studies for analysis. The findings indicate that the reviewed studies were predominantly quasi-experimental, complemented by Classroom Action Research and Research and Development approaches, and were implemented across various elementary mathematics topics. Furthermore, the RADEC model positively contributes to students' mathematical problem-solving ability by enhancing conceptual understanding, mathematical thinking, mathematical communication, learning achievement, and learning interest. Therefore, the RADEC model can be considered an effective instructional alternative for improving elementary school students' mathematical problem-solving ability.